2015
DOI: 10.1108/bfj-03-2014-0132
|View full text |Cite
|
Sign up to set email alerts
|

Consumer perceptions and motivations in choice of minimally processed vegetables

Abstract: Purpose -The purpose of this paper is to examine the usefulness of integrating measures of motivations in predicting purchase intentions of fresh cut products. In order to gain this purpose the authors developed a field study that involved about 425 consumers of fresh cut vegetables products. Design/methodology/approach -Questionnaire data were gathered in Italy on a Likert scale. Questions focussed on intentions to purchase fresh cut lamb's lettuce from environmental sustainable farms, simulating a fresh cut … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 94 publications
0
34
0
Order By: Relevance
“…In addition, health consciousness has been found to predict attitude, intention and purchase of organic foods (Magnusson, Avrola, Hursti Koivisto, Aberg, & Sjoden, 2001. Although the relationship between health consciousness and attitude has not been uniformly supported in all studies (Tobler, Visschers, & Siegrist, 2011), the effects of the construct, as antecedent of attitude towards a minimally processed Eco-labelled vegetable product, in a sample of consumers in Italy revealed that this "new demand" for healthy products can be satisfied by the minimally processed vegetable products (Nassivera & Sillani, 2015). This kind of information depicts a consumer who accepts new technology applied in food production in order to gain peculiarities of healthy food.…”
Section: Health and Green Consciousness As Determinants In Consumer Cmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, health consciousness has been found to predict attitude, intention and purchase of organic foods (Magnusson, Avrola, Hursti Koivisto, Aberg, & Sjoden, 2001. Although the relationship between health consciousness and attitude has not been uniformly supported in all studies (Tobler, Visschers, & Siegrist, 2011), the effects of the construct, as antecedent of attitude towards a minimally processed Eco-labelled vegetable product, in a sample of consumers in Italy revealed that this "new demand" for healthy products can be satisfied by the minimally processed vegetable products (Nassivera & Sillani, 2015). This kind of information depicts a consumer who accepts new technology applied in food production in order to gain peculiarities of healthy food.…”
Section: Health and Green Consciousness As Determinants In Consumer Cmentioning
confidence: 99%
“…In this way the extent of consumers' environmentally friendly behaviors can be facilitated or inhibited by acts of marketers. For instance, it is difficult to buy environmentally friendly food products when they are not available at the local market (Nassivera & Sillani, 2015). This leads to the question as to how green products may be defined.…”
Section: Health and Green Consciousness As Determinants In Consumer Cmentioning
confidence: 99%
See 3 more Smart Citations